Concurrence of overt Cushing’s syndrome and primary aldosteronism accompanied by aldosterone-producing cell cluster in adjacent adrenal cortex: case report - Fushimi, Yoshiro; Tatsumi, Fuminori; Sanada, Junpei; Shimoda, Masashi; Kamei, Shinji; Nakanishi, Shuhei; Kaku, Kohei; Mune, Tomoatsu; Kaneto, Hideaki (BMC Endocrine Disorders, 2021)
Background Various adrenal disorders including primary aldosteronism and Cushing’s syndrome lead to the cause of hypertension. Although primary aldosteronism is sometimes complicated with preclinical Cushing’s syndrome, concurrence of overt Cushing’s syndrome and primary aldosteronism is very rare. In addition, it has been drawing attention recently that primary aldosteronism is brought about by the presence of aldosterone-producing cell cluster in adjacent adrenal cortex rather than the presence of aldosterone-producing adenoma. Case presentation A 67-year-old Japanese female was referred to our institution due to moon face and central obesity. Based on various clinical findings and data, we diagnosed this subject as overt Cushing’s syndrome and primary aldosteronism. Furthermore, in immunostaining for cytochrome P450 (CYP) 11B1, a cortisol-producing enzyme, diffuse staining was observed in tumorous lesion. Also, in immunostaining for CYP11B2, an aldosterone-producing enzyme, CYP11B2 expression was not observed in tumorous lesion, but strong CYP11B2 expression was observed in adjacent adrenal cortex, indicating the presence of aldosterone-producing cell cluster. Conclusions We should bear in mind the possibility that concurrence of overt Cushing’s syndrome and primary aldosteronism is accompanied by aldosterone-producing cell cluster in adjacent adrenal cortex.